The unexpected joy of being sober - Gray, Catherine (Aster, 2017)
"Ever sworn off alcohol for a month and found yourself drinking by the 7th? Think there's 'no point' in just one drink? Welcome! There are millions of us. 64% of Brits want to drink less... Catherine Gray was stuck in a hellish whirligig of Drink, Make horrible decisions, Hangover, Repeat. She had her fair share of 'drunk tank' jail cells and topless-in-a-hot-tub misadventures. But this book goes beyond the binges and blackouts to deep-dive into uncharted territory: What happens after you quit drinking? This gripping, heart-breaking and witty book takes us down the rabbit-hole of an alternative reality. A life with zero hangovers, through sober weddings, sex, Christmases and breakups. In The Unexpected Joy of Being Sober, Catherine Gray shines a light on society's drink-pushing and talks to top neuroscientists and psychologists about why we drink, delving into the science behind what it does to our brains and bodies. Much more than a tale from the netherworld of addicted drinking, this book is about the escape, and why a sober life can be more intoxicating than you ever imagined."--Publisher description.